Climate anxiety, coping strategies and planning for the future in environmental degree students in the UK - Daeninck, Cami; Kioupi, Vasiliki; Vercammen, Ans (Frontiers in Psychology, 2023)
There is increasing recognition of the mental health burden of climate change and the effects on general well-being, even in those who have not (yet) experienced direct impacts. Climate anxiety, which is prominent among young people in particular, describes a state of heightened distress about the (future) effects of climate change. Despite evidence of a link between engagement in climate change issues and heightened climate anxiety, there is a dearth of knowledge on how this affects emerging professionals preparing for careers in the environmental sector. Furthermore, there is a paucity of literature regarding the extent to which young adults are coping with their thoughts and feelings about climate change, and the extent to which they consider climate change in making future plans. The aim of this study was to understand the occurrence and personal management of climate anxiety in UK university students through an online questionnaire. This study was the first to investigate the association between climate anxiety, coping strategies and future planning in university students. Environmental degree students (n = 249) reported greater levels of climate anxiety, more frequent employment of all three examined coping strategies and in particular considered climate change as a factor in their career plans, as compared to their non-environmental degree counterparts (n = 224). Problem-focused coping was the most commonly endorsed strategy, although the prior literature on coping suggests that this may not be sustainable for individually intractable problems. Highly climate-anxious students were more likely to consider climate change in all five decision-making domains, including family planning, long-term habitation, career, financial and travel decisions. This study has identified a need to communicate effective climate anxiety coping strategies to environmental practitioners, university students and educators. Additional research is required to validate the study findings and investigate what motivates students to incorporate climate change into future plans.